Fighting meningococcal disease - Media One production; Aquarius Health Care Videos (Sherborn, MA : Aquarius Health Care Videos, 2004)
This program is a comprehensive and practical guide to meningococcal disease--how to recognise the symptoms, what to do, and what precautions to take
Title from title screen
DVD format
Keywords: Meningitis; Meningitis, Cerebrospinal